2020
DOI: 10.1111/febs.15486
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of vascular damage by systemic dissemination of the oral pathogen Porphyromonas gingivalis

Abstract: Several studies have shown a clear association between periodontal disease and increased risk of cardiovascular disease. Porphyromonas gingivalis (Pg), a key oral pathogen, and its cell surface-expressed gingipains, induce oedema in a zebrafish larvae infection model although the mechanism of these vascular effects is unknown. Here, we aimed to determine whether Pg-induced vascular damage is mediated by gingipains. In vitro, human endothelial cells from different vascular beds were invaded by wild-type (W83) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 55 publications
1
46
0
1
Order By: Relevance
“…PECAM1 is found to be a co-modulator of T-cell immunity (Huang et al, 2017) and a promoter of endothelial junctional integrity (Marelli-Berg et al, 2013). Periodontal pathogens, particularly P. gingivalis, can induce vascular damage through the degradation of PECAM1 (Yun et al, 2005;Farrugia et al, 2020). A protective effect of PECAM1 was also detected in transplant arteriosclerosis (Ensminger et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…PECAM1 is found to be a co-modulator of T-cell immunity (Huang et al, 2017) and a promoter of endothelial junctional integrity (Marelli-Berg et al, 2013). Periodontal pathogens, particularly P. gingivalis, can induce vascular damage through the degradation of PECAM1 (Yun et al, 2005;Farrugia et al, 2020). A protective effect of PECAM1 was also detected in transplant arteriosclerosis (Ensminger et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, polymicrobial infection with Pg, Td, Tf, and Fn is associated with accelerated atherosclerosis in vivo [100,101]. Recent studies showed that Pg is able to increase vascular permeability and cause vascular damages via, respectively, its outer membrane vesicles and surface-expressed gingipains in vitro and in vivo in a zebrafish model [102]. Also, Pussinen et al found that coronary heart disease is more common in people who have anti-Pg antibodies compared to those who do not, suggesting that periodontal infection or the host's response to anti-Pg infection could play a role in the pathogenicity of coronary heart disease [103,104].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…They may also be an early sign of therapeutic escape or disease relapse. People suffering from IBD are characterized by dysbiotic oral and gut microbiota with a decrease in bacterial diversity, a decrease in the abundance of Firmicutes phylum, and an increase in the abundance of Proteobacteria and Bacteroidetes phylum [102,[177][178][179]. Recent studies showed that, compared to healthy people, these people also presented an oral dysbiosis and that periodontitis was significantly associated with IBD [180,181].…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…As gingipains are proteolytic enzymes, they cause bacterial virulence by activating matrix metalloproteinases such as MMP-1, MMP-3, and MMP-95, and by degrading extracellular matrix host proteins such as collagen, fibronectin, and laminin. Gingipains also lead to increased vascular permeability and the degradation of complement factors [ 33 , 34 ].…”
Section: Periodontitis and Systemic Complicationsmentioning
confidence: 99%